Sustained-Release Fillers for Dentin Disinfection: An Ex Vivo Study - Bernhard Funk; Sharonit Sahar-Helft; David Kirmayer; Michael Friedman; Doron Steinberg (Hindawi Limited, 2019)
Enterococcus faecalis is the most commonly recovered species from failed root canal treatments. In this study, we tested the capability of a novel intracanal sustained-release filler (SRF) containing cetylpyridinium chloride (CPC) to disinfect dentinal tubules of segmented human tooth specimens. Human dental root specimens were infected with E. faecalis V583 for 3 weeks in a static environment. The tested intracanal medicaments were SRF-CPC and calcium hydroxide (CH). Each medicament was introduced into the canal of the dental specimen and incubated for 7 days. The bacteriological samples were taken by shaving the dentine surrounding the root canal with dental burs ranging in size from ISO 014-020. The obtained dentine powder was collected in test tubes containing phosphate-buffered saline, sonicated, and plated on agar plates. Colony-forming units were counted after 48 h of incubation. Random specimens were also examined under confocal laser scanning microscopy and scanning electron microscopy. A statistical difference was found in the bacterial counts obtained from all layers of infected dentin between the control and the SRF-CPC groups. CH reduced bacterial viability significantly only in the first layer of the infected dentin, up to 150 μm into the dentinal tubules. CLSM images showed that SRF-CPC killed most bacteria throughout the infected dentin up to 700 μm of penetration. SEM images demonstrated the adhesion ability of SRF-CPC to the dentinal wall. In conclusion, SRF-CPC is a potential intracanal medicament for disinfecting dentinal tubules.